An Innovative MOCAF Dryer Design: A TRIZ-Driven Solution - Hermanuadi, Didiek; Iswahyono, Iswahyono; Wibisono, Yossi; Triardianto, Dimas; Djamila, Siti; Bahariawan, Amal (International Journal of Technology, Food and Agriculture, 2025)
The drying stage critically determines the quality of Modified Cassava Flour (MOCAF), directly affecting its functional properties. Insufficient moisture removal leads to detrimental effects including structural degradation and microbial proliferation, while over-drying promotes oxidation. Existing drying methods lack precision and reproducibility, underscoring the need for a MOCAF-specific dryer system. The central challenge is to develop a drying method that is both rapid and efficient while simultaneously preserving product quality. This study aimed to design an optimized drying model for micro-, small-, and medium-sized enterprises (MSMEs), leveraging a TRIZ-driven innovation process to enhance MOCAF quality and process efficiency. Applying TRIZ facilitated the systematic identification and resolution of conflicting design parameters (e.g., rapid drying vs. product integrity). A hybrid technology model was then developed—combining infrared heating, forced-air circulation, and LPG combustion. Performance was evaluated in a pilot unit capable of drying 50 kg of wet MOCAF per six-hour batch, under controlled conditions: 76 °C drying temperature, 2.1 m³/min airflow, and 413 g/h LPG consumption. The optimized dryer achieved a water removal rate of 315 g H₂O/hour. Comparative benchmarking against conventional sun and cabinet dryers showed the hybrid system significantly reduced drying time while maintaining superior structural and functional properties. The TRIZ-based, hybrid MOCAF dryer offers a scalable, cost-effective solution tailored to MSMEs. By closing the innovation loop—linking TRIZ principles directly to enhanced performance metrics—this study delivers practical, field-ready technology. Key contributions include the first documented integration of infrared, forced-air, and LPG heating in MOCAF drying, optimized process parameters, and clear industrial applicability.